Hubungan Aktivitas Fisik Pola Makan dan Literasi Kesehatan Terhadap Fungsi Kognitif Usia Dewasa - Nurul Ichsania; Nurussyariah (Indonesian Journal of Physical Activity, 2026)
Cognitive function is an essential component of overall health that influences productivity, decision-making, memory, and quality of life during adulthood. Modifiable lifestyle factors, including physical activity, dietary patterns, and health literacy, are believed to play important roles in maintaining cognitive function. This study aimed to examine the relationship between physical activity, dietary patterns, and health literacy and cognitive function among adult women attending Femme Fit Fitness Center. An analytical observational study with a cross-sectional design was conducted involving 35 adult women selected through purposive sampling. Physical activity was assessed using the International Physical Activity Questionnaire-Short Form (IPAQ-SF), dietary patterns were evaluated using a Food Frequency Questionnaire (FFQ), health literacy was measured using the Health Literacy Survey Questionnaire (HLS-EU-Q16), and cognitive function was assessed using the Montreal Cognitive Assessment Indonesian Version (MoCA-Ina). Data were analyzed using the Chi-square test with a significance level of p<0.05. The results showed significant associations between physical activity (p=0.015), dietary patterns (p=0.031), health literacy (p=0.023), and cognitive function. Participants with higher physical activity levels, healthier dietary patterns, and better health literacy tended to demonstrate better cognitive function. These findings suggest that promoting healthy lifestyles and improving health literacy may contribute to maintaining cognitive health among adult women.